2009
DOI: 10.1590/s0101-20612009000400033
|View full text |Cite
|
Sign up to set email alerts
|

Molho cremoso à base de extrato de soja: estabilidade, propriedades reológicas, valor nutricional e aceitabilidade do consumidor

Abstract: O aumento do consumo de soja (principalmente das bebidas à base de soja, que tiveram um incremento de 30%) pode estar relacionado à percepção favorável do consumidor em relação à alta qualidade da proteína e o baixo nível de óleo e colesterol dos produtos de soja (LAKSHMANAN;LAMBALLERIE;JUNG, 2006).A busca do consumidor por alimentos mais nutritivos tem sido observada como tendência no mundo globalizado, favorecendo as pesquisas de desenvolvimento de produtos que atendam a tal anseio (SLOAN, 2005;STEWART-KNOX;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 6 publications
(8 reference statements)
2
7
0
4
Order By: Relevance
“…This behavior is confirmed by the reduction in product viscosity as the shear rate increases ( Figure 5B) (Schramm, 2000). The same behavior was observed by Campos et al (2009) for soy based creamy sauce and by Coutinho & Cabello (2005) for cassava starch gels with 6% to 10% starch. Table 2 presents the values of the parameters for the fits of the rheological models to the creamy paste's flow experimental data.…”
Section: Product Characterizationsupporting
confidence: 77%
See 3 more Smart Citations
“…This behavior is confirmed by the reduction in product viscosity as the shear rate increases ( Figure 5B) (Schramm, 2000). The same behavior was observed by Campos et al (2009) for soy based creamy sauce and by Coutinho & Cabello (2005) for cassava starch gels with 6% to 10% starch. Table 2 presents the values of the parameters for the fits of the rheological models to the creamy paste's flow experimental data.…”
Section: Product Characterizationsupporting
confidence: 77%
“…For this attribute, the first two components explain 89.86% of the variability in the responses. Campos et al (2009) obtained a similar result on the sensory evaluation of the acceptance for soy based creamy sauce. The authors observed no significant difference between the three formulations elaborated for texture.…”
Section: Internal Preference Mappingsupporting
confidence: 59%
See 2 more Smart Citations
“…Os polissacarídeos são polímeros naturais constituídos por um ou por diferentes monossacarídeos (CUNHA et al, 2009 A carboximetilcelulose, na indústria alimentícia, é empregada como espessante, estabilizante e agente de corpo. Contribui para melhorar a consistência dos alimentos e, em certos casos, melhora os aspectos nutricionais (CAMPOS et al, 2009;CALEGUER e BENASSI, 2007). …”
Section: Carboximetilceluloseunclassified